Who Enjoys Teaching, and When? Between- and Within-Person Evidence on Teachers’ Appraisal-Emotion Links - Frenzel, Anne C.; Fiedler, Daniel; Marx, Anton K. G.; Reck, Corinna; Pekrun, Reinhard (Frontiers in Psychology, 2020)
Testing assumptions proposed by Frenzel’s reciprocal model of teacher emotions (e.g., Frenzel, 2014), this study explored relations between teachers’ appraisals concerning the attainment and importance of their teaching goals and their emotions. Specifically, we addressed teachers’ goals of high student performance, motivation, discipline, and high-quality teacher-student relationship and three key discrete emotions, namely enjoyment, anger, and anxiety during teaching. N = 244 secondary school teachers (70.1 % female) self-reported their goal attainment and importance appraisals and emotional experiences with respect to up to three different classes they currently taught. Results from single- and two-level multivariate multiple regression analyses largely supported the relevance of the goal attainment appraisals for teachers’ emotions both on the between-person and the within-person level. Goal importance appraisals proved to be of secondary relevance. On the between-person level, those teachers who positively appraised the attainment of motivation, discipline, and teacher-student relationship quality proved to report more enjoyment, and les anxiety and anger. On the within-person level, teachers reported enjoying teaching those classes more, which they perceived as better performing, more motivated and disciplined, and with whom they had a better relationship. Anger and anxiety were negatively linked to appraisals pertaining to the attainment of discipline and teacher-student relationship quality. Across both analyses perspectives, teacher-student relationship quality attainment showed particularly strong links with all three emotions. Since teachers’ subjective evaluations regarding student behaviors were shown to be highly relevant for their emotions, we conclude that teachers could be supported in modifying their emotional experiences through cognitive reappraisal. Interventions targeting teachers’ relationships with students, and their cognitive judgements thereof, seem particularly promising.